PROFILE OF CYTOTOXICITY IN HepG2 CELLS AND THE POTENTIAL FOR MODULATION OF PANCREATIC CELLS BY PINEAPPLE CROWN FRACTION (Ananas comosus (L.)Merr) IN DIABETIC RATS - Winartiana Winartiana; Okky Intan Mawarni; Iftinah Harini; Erlina Putri Lestari (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
The ethyl acetate fraction of pineapple crown, Ananas comosus (L.) Merr is known to contain flavonoid secondary metabolites with potential antidiabetic activity. Flavonoids have been widely reported to have potent antidiabetic effects through antioxidant activity and pancreatic cell-protective mechanisms. This study aimed to evaluate the in vitro toxicity profile of the ethyl acetate fraction using HepG2 cells and its in vivo antidiabetic efficacy in an alloxan-induced diabetic rat model. Cytotoxicity was assessed using the MTT assay, with Doxorubicin HCl used as a positive control. The in vivo study involved 35 male Wistar rats divided into seven groups: a negative control, a positive control (glibenclamide 0.45 mg/kgBW), and five treatment groups receiving the ethyl acetate fraction at doses ranging from 10 to 25 mg/kgBW. The evaluated parameters included changes in body weight, blood glucose levels, and pancreatic α- and β-cell counts. The cytotoxicity assay showed that the ethyl acetate fraction exhibited an IC50 value of 287.14 µg/ml, indicating relatively low toxicity compared with Doxorubicin HCl (IC50 =43.25 µg/ml). In vivo administration of the ethyl acetate fraction, particularly at a dose of 22 mg/kgBW, produced the most optimal effects, as indicated by body weight recovery toward normal values, a significant reduction in blood glucose levels, a decrease in pancreatic α-cell count (40±1.7), and an increase in β-cell number (48 ± 1.7) (p < 0.05). The ethyl acetate fraction of Ananas comosus (L.) Merr demonstrates antidiabetic potential by improving islet cell profiles while exhibiting moderate cytotoxicity in vitro, suggesting its potential for further development as an antidiabetic therapeutic agent.